(untitled) (Bangladesh Journal of Agricultural Research, 2026)
High yield and stability are prerequisites for crop improvement and adaptation. Genotype + genotype × environment has been used to study G × E interaction in multi-environments, thus, this trial addressed selection for bast and core fibres yields and yield stability of kenaf. Fourteen kenaf genotypes were assessed in six diverse locations in Nigeria in a randomized complete block design with three replications for two years. Fibres weight data were pooled across the two years and subjected to GGE bi-plot analysis. Significant differences existed among the bast and core fibre yields of the genotypes in the locations. Genotype SAU75-441 produced the highest mean bast fibre yield (2.80 t ha-1) while GS14-52 and AEHC-3 were also promising with respect to bast fibre production across locations. Core fibre yields of SAU75-441, GS14-52, AEHC-3, AU75-452 and AU 24524 were greater 4.00 t ha-1. Hence, SAU75-441, GS14-52 and AEHC-3 are identified for further consideration for their yield potentials. Orin Ekiti and Ikenne had higher bast yields (2.55 t ha-1) and (2.52 t ha-1), respectively with core fibre yields (4.48 t ha-1) and (4.29 t ha-1), respectively. The bi-plot identified Ikenne, Ilora, Iwo and Orin Ekiti as a mega-environment where genotype SAU75-441 was the vertex for both bast and core fibres. Genotype GS14-52 was the vertex genotype in the Kaduna and Kisi mega-environment for the fibres. Genotypes SAU75-441, GS14-52 and AEHC-3 were therefore considered most suitable for the respective environments. Genotypes SAU75-414 and GS14-52 were highest bast and core fibres yields, and most stable with broadest adaptation in the two fibre types, hence, they are best recommended for future crop improvement programme. Bangladesh J. Agril. Res. 48(1): 101-114, March 2023